Clinical characteristics and outcome of patients admitted during the first and second waves of COVID-19 pandemic at a Tertiary Hospital in Lagos, Nigeria - Iorhen Ephraim Akase; Patricia Eyanya Akintan; Erereoghor Otrofanowei; Oluwarotimi Bolaji Olopade; Gbenga Olorunfemi; Adefolarin Opawoye; Felix M Alakaloko; Uyiekpen Emmanuel Ima-Edomwonyi; Yeside Olubunmi Akinbolagbe; Osigwe Paul Agabi; Danladi Abraham Nmadu; Gbemileke O Akinbode; et al. (Journal of Clinical Sciences, 2023)
Introduction: Clinical data on the differences in presentation and outcome of admitted COVID-19 patients in Nigeria are limited. This study aimed to compare the first and second waves of the COVID-19 pandemic in a Tertiary Hospital in Lagos and describe the clinical differences between the waves, the severity of COVID-19, and the mortality differences. Methods: The study was a retrospective review of the medical records of all children and adults admitted to the Lagos University Teaching Hospital (LUTH) COVID-19 Isolation and Treatment Centre during the first wave (from April 2020 to October 2020) and second wave (from December 2020 to April 2021). The clinical characteristics (including COVID severity) and outcome among admitted patients during the two waves were compared. Results: Between April 2020 and April 2021, 602 patients were admitted to LUTH for COVID-19. Patients in the first wave were significantly younger (43 vs. 54.5 years), more in number (53.8% vs. 46.2%), and had a higher proportion of health-care workers than those in the second wave (14.5% vs. 6.5%). Comorbidities were present in more than half of the patients hospitalized for COVID-19 infection (51.0%). This proportion was much higher during the pandemic's second wave (41.7% vs. 61.9%, P < 0.001). The most common comorbidity found in hospitalized patients was hypertension (37.0%). Patients admitted during the second wave had shorter stays (11 vs. 7 days) and similar mortality rates (10.2% vs. 10.8%). Conclusion: The first and second waves had comparable mortality rates though patients in the first wave were younger and there were more healthcare providers in the cohort. Patients admitted to the second wave however had more comorbidities but shorter lengths of stay which may suggest a better understanding of the infection and better outcome.